Health literacy meets the life-course perspective: towards a conceptual framework - Helle Terkildsen Maindal; Jens Aagaard-Hansen (Taylor & Francis Group, 2020)
This paper presents a novel conceptual framework combining the concepts of health literacy and life-course to guide public health planning and research. Health literacy is a key competence that enables individuals to navigate health-care systems and health promotion activities. The life-course perspective places emphasis on how disease risk accumulates along the life trajectory from fetal life onwards, and how it can even pass from one generation to the next. Our conceptual framework illustrates how different domains of health literacy are required, and how the unequal distribution of health literacy may be influenced by social determinants at different times in the life-course. Thus, it is essential to disaggregate health literacy into sub-themes and analyse them as they unfold in a long-term life-course perspective. The suggested framework would allow these patterns to be mapped, thereby enabling public health planners to strategically target health literacy promotion programmes to the right population segments at the right time.